2020
DOI: 10.3357/amhp.5439.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Inhibition and Exposure to Organophosphate Esters in Aircraft Maintenance Workers

Abstract: INTRODUCTION: Aircraft maintenance workers may be exposed to organophosphates in hydraulic fluid and engine oil. Previous research has indicated that inhalation may not be the primary exposure route. This study sought to measure dermal contact and inhalation in conjunction with cholinesterase inhibition and determine if Air Force Specialty Code serves as an exposure predictor.METHODS: Aircraft maintenance workers were sampled for changes in acetylcholinesterase and butyrylcholinesterase. Dermal contact was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Silicone samplers are being used increasingly as passive monitoring devices for assessing multipollutant exposures in a variety of settings including occupational, vulnerable populations (such as children and pregnant women , ), pet cats and dogs, beehives, wild frogs, and their habitats . Furthermore, previous studies have demonstrated that chemicals measured on wristbands are significantly associated with human and canine exposure biomarkers, reinforcing their utility. ,,,,, Silicone wristbands are a useful tool for investigating personal exposures that occur via inhalation and through dermal routes .…”
Section: Introductionmentioning
confidence: 99%
“…Silicone samplers are being used increasingly as passive monitoring devices for assessing multipollutant exposures in a variety of settings including occupational, vulnerable populations (such as children and pregnant women , ), pet cats and dogs, beehives, wild frogs, and their habitats . Furthermore, previous studies have demonstrated that chemicals measured on wristbands are significantly associated with human and canine exposure biomarkers, reinforcing their utility. ,,,,, Silicone wristbands are a useful tool for investigating personal exposures that occur via inhalation and through dermal routes .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the TPHP median levels for crew chiefs were 434 ng/g normalized for 24 h with maximum level of 2584 ng/g per 24 h (corresponding to approximately median levels of 2300 ng/band and maximum level of 13,700 ng/band with equivalent band weights in both studies), which is considerably higher taking the shorter sampling period into account (1 day vs 5 days), in turn suggesting occupational exposure. A recent study investigated OPEs levels among US military aircraft maintainers, also using silicone bands as passive samplers, measuring an average of 1.67 ng/g of TNBP, 832.4 ng/g of TPHP, and 2352.1 ng/g of TMPP for a shift work of crew chiefs (n = 14) 29 , 30 , showing a similar trend in prevalence and level as the crew chiefs in our study (mean exposure levels were 49 ng/g TNBP, 622 ng/g TPHP and 959 ng/g TMPP, respectively). However, in the Hardos et al report, crew chief was not the job function with the highest mean levels for any of these three OPEs assessed, since aerospace propulsion, fuel system repair and avionics presented higher or equivalent mean levels for each of the OPEs 29 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Hardos et al report, crew chief was not the job function with the highest mean levels for any of these three OPEs assessed, since aerospace propulsion, fuel system repair and avionics presented higher or equivalent mean levels for each of the OPEs 29 . Overall, Hardos et al suggested that the use of job functional career code system for aircraft maintenance employees was not a good predictor of exposure 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, significant positive and negative associations existed between several PBDEs, and NFRs concentration and free thyroxine (FT4), free triiodothyronine (FT3), and thyroid-stimulating hormone (TSH) ( Wang et al, 2020 ). Two other studies focused on occupational exposure of aircraft workers, which included evaluating the association between OPE exposure with cholinesterase inhibition ( Hardos et al, 2020 ), and evaluating OPE as well as PAH exposure on lung function, systemic inflammation, and genetic damage ( Andersen et al, 2021 ); but in both instances significant associations were not seen.…”
Section: Use Of Personal Silicone Samplers To Assess Health Risksmentioning
confidence: 99%
“…Multiple studies demonstrated the usefulness on using silicone wristbands to assess exposure both in rural setting ( Varnell et al, 2021 ; Vidi et al, 2017 ) and in children ( Lipscomb et al, 2017 ; Vidi et al, 2017 ). Additionally, silicone wristbands have been successful exposure assessment tools when deployed only in occupational settings ( Varnell et al, 2021 ; Andersen et al, 2021 ; Hardos et al, 2020 ) and have demonstrated the relationship between occupational exposure to environmental contaminants and adverse health outcomes ( Varnell et al, 2021 ). If silicone wristbands are deployed only while an individual is in an occupational setting, occupational exposure can be separated from total exposure.…”
Section: Use Of Personal Silicone Samplers To Assess Health Risksmentioning
confidence: 99%